Effect of edible coatings of polysaccharide-protein-lipid structure on andean blackberry - Camilo Villegas Yépez; Misael Cortés Rodríguez; William Albarracín Hernández; Pablo Emilio Rodríguez Fonseca (Dyna, 2019)
Edible coatings (EC) have shown advantages in fruit preservation. The influence of an EC based on a polysaccharide-protein-lipid structure (Cassava starch: CS, whey protein: WP, and beeswax: BW), glycerol (G), stearic acid (SA) and chitosan (CH), on texture and weight loos of blackberry stored at 4 and 25 °C was evaluated. A composite central design was used considering the independent variables: CS (3.0-3.5%), WP (0.5-1.5%), BW (0.0-0.5%). The experimental optimization defined the formulation: CS (3.50%), WP (1.16%), BW (0.47%); and CH (0.5-1.0%) was added again evaluating the fruit during storage until visual infection was observed. Results indicated that the best concentration of CH (0.75%) did not present visual infection until day 10 of storage at 4 °C and reduce weight loss with respect to other treatments